Organisational coaching to improve workplace resilience: a scoping review and agenda for future research - Sipondo, Abongile; Terblanche, Nicky (Frontiers in Psychology, 2024)
In an increasingly demanding and pressured work environment, employee resilience is acknowledged as a critical element to navigate adversity. There has been increased focus and interest in studying the nature of resilience in the workplace, however the mechanisms of developing and sustaining resilience are still under debate. Coaching is a promising method organisations use to improve employee resilience and provides employees with support to deal with the challenging working environment. There has been significant interest in coaching for resilience in recent years, however there is no overarching, consolidated view on the nature and dynamics of resilience coaching. This scoping review seeks to fill this gap by making three contributions. Firstly, we present details on various types of coaching approaches used to improve resilience. Secondly, we review the specific coaching elements and processes that lead to improved resilience and finally, we provide an overview on the efficacy of resilience coaching interventions. We conclude this scoping review with a roadmap for future research to help position and strengthen organizational coaching as a pillar of resilience development. This scoping review followed a five-stage PRISMA-ScR methodology which entails formulating research questions; identifying studies; choosing studies; extracting and charting data; and summarising the findings.